2023
DOI: 10.3390/su15043073
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vegetation Dynamics in the Three-North Region of China to Climate and Human Activities from 1982 to 2018

Abstract: To tackle ecological problems, many ecological restoration projects have been implemented in northern China. Identifying the drivers of vegetation change is critical for continued ecological engineering. In this study, three typical ecological reserves in the Three-North Shelter Forest Program Region (TNSFR) were selected to identify their vegetation development characteristics and driving mechanisms using the normalized difference vegetation index (NDVI), climate factors, and land use data. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Observations of the NDVI via remote sensing satellites are susceptible to various factors that may affect data quality. The annual maximum method is commonly employed [49]. This method utilizes the following calculation formula:…”
Section: Retrieval Of Fvc Time Series Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Observations of the NDVI via remote sensing satellites are susceptible to various factors that may affect data quality. The annual maximum method is commonly employed [49]. This method utilizes the following calculation formula:…”
Section: Retrieval Of Fvc Time Series Datamentioning
confidence: 99%
“…It is commonly assumed that FVC is affected by the combined impact of two factors: human activities and climate variability [26,27,29,35,58,[60][61][62][63]. The response of vegetation conditions to temperature and precipitation is often nonlinear [41].…”
Section: Calculating Contribution Of Driving Factors To Variation In Fvcmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Trend analysis was used to identify areas with significant increase in NDVI in Inner Mongolia from 2000 to 2020. Trend analysis is a linear regression analysis of time-dependent variables [27,28]. The constantly changing properties of the vegetation may be reflected in the trend of the change in NDVI for each grid by applying linear trend analysis.…”
Section: Identifying the Afforestation Regionsmentioning
confidence: 99%
“…They found that the impact of population density and GDP on vegetation NPP was more significant than that of climatic factors such as precipitation [29]. In recent years, societal policies such as ecological engineering have played an increasingly significant role in influencing terrestrial vegetation [30]. Cai et al (2023) employed the RF method to identify the primary drivers of changes in NPP in China, attributing them mainly to human activities, particularly afforestation and other ecological engineering endeavors [31].…”
Section: Introductionmentioning
confidence: 99%